Exploring Music-Based Interventions for Executive Functioning and Emotional Well-Being in Stroke Rehabilitation: A Scoping Review - Camila F. Pfeiffer; Wendy L. Magee; Rebecca Fülöp; Travis C. Nace; Candela Castro; Agustina Iturri; Jimena Franceschi; Gabriela Echauri; Liliana Gassull; María Julieta Russo (NeuroSci)
Purpose: Stroke is one of the leading causes of disability with life-long implications requiring assessment and treatment of several functional domains. This review identifies the results from research into music-based interventions (MBIs), including music therapy (MT), for executive functions (EFs) and emotional well-being (EWB) in adults with stroke and highlights opportunities for clinical practice and future research. Methods: APA PsycInfo (EBSCOhost), and CINAHL (EBSCOhost) were searched, in addition to grey literature. Results: A total of 49 studies were included and encompassed experimental, analytic, and descriptive observational studies, and case reports, involving a total of 1663 participants. In total, 32 studies included MT interventions, and 17 were MBIs. EFs were an outcome in 20.41%, and EWB in 61.22% of studies, for which active interventions were the most utilized. Overall, 73.47% of the studies reported positive results. Conclusions: This scoping review indicates that music interventions can be beneficial for the improvement of different aspects of EFs and EWB at different stages of stroke recovery. Further research may benefit clinical practice by including standardized protocols, outcome and self-reported measures, and brain imaging data to determine the effects of interventions and support evidence-based decisions for treatment policies for stroke survivors.